KOOP Mini Mart FSK 6 UiTM Puncak Alam / Ahmad Hafizi Ahmar, Ain Madihah Fadzerun … [et al.] - Ahmar, Ahmad Hafizi; Fadzerun, Ain Madihah; Jaafar, Nur Hidayah; Azmi, Mas Hanisah (2018)
Mini Koop is one of the shops in Faculty Health Science Of UiTM Puncak A|am. This shop sells variety of items including foods, beverages, stationary, beauty accessories and also printing service. As the place of the shop is not strategic and small space, this contributes to problems to this shop. Nevertheless, the major problems of this shop is too many competitors as there were others shop at that area that more strategic. Thus, there are some solution to solve this problems including give flyers to students, manage the shop properly but the best solution is to expose the shop through internet website, social media likes instagram, twitter and whatsapp as students nowadays are more toward advance technology. Thus, the shop can promote their items through the website and social media which can make student know the existence of the shop and enliven the shop by having many customers come to the shop.